Preparation method of battery cathode material as well as cathode material and application thereof

The preparation of dual-function FeNi single-atom catalysts through parallel spinning technology and high-temperature calcination process has solved the problem of difficult realization of dual-function catalysts in zinc-air battery cathode materials, and significantly improved the electrochemical performance of zinc-air battery.

CN119481101AActive Publication Date: 2025-02-18CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
CN202510052633.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

It is difficult to prepare dual-function oxygen reduction (ORR) and oxygen precipitation (OER) catalysts for zinc-air battery cathode materials, resulting in low efficiency in charge and discharge process of zinc-air battery and large voltage gap.

Method used

The dual-function FeNi single-atom catalyst is prepared by parallel spinning technology combined with high-temperature calcining technology. This method uses electrospinning technology to spin Fe-ZIF-8 and Ni-ZIF-8 seeds into nanofibers and calcined at high temperature to form a bifunctional catalyst based on carbon fibers.

Benefits of technology

The uniform distribution and high catalytic activity of the dual-function catalyst are achieved, which reduces the energy efficiency poor during the charging and discharging process, and improves the open circuit voltage and peak power density of the zinc air battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481101A_ABST
    Figure CN119481101A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a battery cathode material as well as the cathode material and application thereof, and belongs to the technical field of batteries. The preparation method comprises the following steps: respectively preparing Fe-ZIF-8 seed crystal and Ni-ZIF-8 seed crystal into spinning solutions, respectively putting the spinning solutions into two spinning needle tubes which are arranged in parallel, carrying out electrostatic spinning, and carrying out high-temperature calcination at 950-1000 DEG C to obtain a catalyst; the catalyst is prepared into catalyst slurry, and the catalyst slurry is dispensed on carbon cloth to obtain the battery cathode material. According to the invention, the problem of coverage between active components caused by preparation of a bifunctional catalyst by a traditional physical mixing method is avoided, full exposure of bifunctional active sites is realized, and a new method is provided for a cathode material of a rechargeable zinc-air battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method and application of a battery cathode material. Background Art

[0002] As the global energy crisis and environmental pollution become increasingly severe, the development of clean and efficient energy storage and conversion devices has become particularly urgent. Zinc-air batteries stand out among many energy storage systems due to their inherent safety, environmental friendliness and high theoretical energy density (1086 Wh / kg), providing power for many emerging applications. For rechargeable zinc-air batteries, the cathode reaction kinetics during discharge and charge are very slow, resulting in a large gap between charge and discharge voltages and poor energy efficiency. Therefore, it is urgent to prepare bifunctional catalysts for oxygen reduction (ORR) and oxygen evolution (OER) that meet the needs of both the charge and discharge processes for zinc-air battery cathode materials.

[0003] It is difficult to achieve dual functions with the same material. Although noble metal (such as Pt, Ru) electrocatalysts are widely used to prepare zinc-air battery cathode materials, they have the problems of high cost and single function. At present, the main technical method for preparing bifunctional battery cathode catalytic materials is to physically mix catalysts with ORR active components and OER active components respectively. This method has the problem of poor compatibility, the inability to control the uniform distribution of the catalyst and the easy coverage of active sites, which hinders the further improvement of the performance of zinc-air batteries. Therefore, designing effective bifunctional electrocatalysts for air cathodes is crucial to accelerate the commercialization of rechargeable zinc-air batteries. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.

[0005] The first aspect of the present invention provides a method for preparing a battery cathode material: Fe-ZIF-8 seed crystals and Ni-ZIF-8 seed crystals are first prepared into spinning solutions and then placed in two spinning needle tubes arranged in parallel for electrospinning. They are then calcined at 950-1000°C to obtain catalysts. Catalyst slurry is made from the catalyst and dripped onto carbon cloth to obtain battery cathode materials.

[0006] As a preferred embodiment of the preparation method of the present invention: the preparation method of the catalyst slurry comprises: mixing the catalyst, ethanol and Nafion solution to obtain the catalyst slurry.

[0007] As a preferred embodiment of the preparation method of the present invention, the applied voltage is 18-22 kV, the spinning rate is 1-1.2 mL / h, and the receiving distance is 12-15 cm.

[0008] As a preferred embodiment of the preparation method of the present invention: the preparation method of the catalyst comprises the following steps: Step 1: Mix zinc salt, iron salt and organic ligand and add them to a solvent to prepare Fe-ZIF-8 seed crystals; Mix zinc salt, nickel salt and organic ligand and add them to a solvent to prepare Ni-ZIF-8 seed crystals; Step 2: mixing the Fe-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution A; mixing the Ni-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution B; Step 3: Spinning solution A and spinning solution B are placed in two spinning needle tubes respectively, and electrospinning is performed using spinning needles arranged in parallel to obtain nanofibers containing FeNi bimetallic; Step 4: pre-oxidize the FeNi bimetallic nanofibers prepared in step 3, then calcine at 950-1000° C., and obtain the catalyst after natural cooling.

[0009] As a preferred embodiment of the preparation method of the present invention: in step 1, the zinc salt is zinc nitrate hexahydrate; the iron salt is iron nitrate nonahydrate; and the nickel salt is nickel nitrate hexahydrate.

[0010] As a preferred embodiment of the preparation method of the present invention: in step 2, the polymer is polyacrylonitrile and polyvinyl pyrrolidone; the spinning solvent is N, N-dimethylformamide; the mass ratio of the Fe-ZIF-8 seed crystals, the polymer, and the spinning solvent is 5~7:3:35~40; the mass ratio of the Ni-ZIF-8 seed crystals, the polymer, and the spinning solvent is 5~7:3:35~40.

[0011] As a preferred embodiment of the preparation method of the present invention: in step 1, the mass ratio of zinc salt, iron salt and organic ligand is 28-35:1:33-40; the mass ratio of zinc salt, nickel salt and organic ligand is 2-3:2:9-11; the organic ligand includes dimethylimidazole; and the solvent includes methanol.

[0012] As a preferred embodiment of the preparation method of the present invention: in step 4, the pre-oxidation heating rate is 1-2°C / min, in air atmosphere, and the pre-oxidation time is 2-3 h; the high-temperature calcination heating rate is 5-6°C / min, in nitrogen atmosphere, and the calcination time is 2-3 h.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention adopts parallel spinning technology combined with high-temperature calcination process to prepare a bifunctional FeNi single-atom catalyst. This preparation method avoids the coverage problem between different catalytic reaction active sites caused by the traditional physical mixing method. In addition, the parallel spinning technology realizes the interaction between the dual catalytic active sites, ensuring that the dual active sites are fully exposed and evenly distributed. The preparation process is simple, the material cost is low, and large-scale production can be achieved.

[0014] (2) The bifunctional FeNi single-atom catalyst material obtained by the parallel spinning technology provided by the present invention has high catalytic activity, and the carbon nanofibers provide a network structure with high conductivity, which accelerates the electron transfer rate. The dual active sites of FeNi ensure the bifunctional activity of the catalyst and present a small ΔE (0.66 V).

[0015] (3) The bifunctional FeNi single-atom catalyst provided by the present invention is used as the air cathode to assemble a rechargeable zinc-air battery, which exhibits a high open circuit voltage (1.53 V) and a high peak power density (252 mW / cm 2 ), which is superior to the bifunctional catalyst prepared by simple physical mixing method, and provides a new method for preparing high-activity bifunctional air cathode materials for rechargeable zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein: Figure 1 This is a physical picture of the cathode electrode material of the sample of Example 1 used in a rechargeable zinc-air battery; Figure 2 This is a scanning electron micrograph of the sample of Example 1; Figure 3 is the X-ray diffraction pattern of the sample in Example 1; Figure 4 LSV test curves of samples of Examples 1 to 3; Figure 5 The open circuit voltage curves of the rechargeable zinc-air battery assembled using the samples of Example 1 and Example 4 as air electrode materials.

[0017] Figure 6 The discharge curves and power density curves of the rechargeable zinc-air batteries assembled using the samples of Example 1, Example 4 and Example 5 as air electrode materials.

[0018] Figure 7 The constant current discharge curves of the rechargeable zinc-air battery assembled with the air electrode material of the sample of Example 1 at different current densities.

[0019] Figure 8The sample of Example 1 was used for the rechargeable zinc-air battery assembled with air electrode materials at 10 mA cm -2 Constant current charge and discharge curves at current density. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0021] Embodiment 1: This embodiment provides a bifunctional FeNi single atom catalyst obtained by parallel spinning technology, and the preparation method is as follows: (1) Add 3.94 g of dimethylimidazole, 3.36 g of zinc nitrate hexahydrate and 120 mg of ferric nitrate nonahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water and dry to obtain Fe-ZIF-8 seed crystals; add 10.59 g of dimethylimidazole, 2.37 g of zinc nitrate hexahydrate and 2.34 g of nickel nitrate hexahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water and dry to obtain Ni-ZIF-8 seed crystals.

[0022] (2) Take 0.35 g of Fe-ZIF-8 seed crystals, 0.07 g of polyvinyl pyrrolidone (Aladdin, P110607) and 0.14 g of polyacrylonitrile (Aladdin, P303197) and dissolve them in 2.45 g of N, N-dimethylformamide solvent to obtain spinning solution A; take 0.35 g of Ni-ZIF-8 seed crystals, 0.07 g of polyvinyl pyrrolidone and 0.14 g of polyacrylonitrile and dissolve them in 2.45 g of N, N-dimethylformamide solvent to obtain spinning solution B. Spinning solution A and spinning solution B are placed in two spinning needle tubes respectively, and two spinning needles arranged in parallel and close to each other are used. The specifications of the two parallel spinning needles are 0.62 mm inner diameter and 0.9 mm outer diameter. Electrospinning is carried out under a high voltage electric field of 18 kV, wherein both spinning solution A and spinning solution B are 2.5 mL, the distance between the spinning needle and the receiving roller is 12 cm, the spinning rate is 1 mL / L, and the nanofiber containing FeNi bimetallic is obtained at room temperature, with a thickness of about 5 µm. It is then placed in an air atmosphere and heated to 280 °C at a heating rate of 1 °C / min for pre-oxidation, maintained for 2 h, and then heated to 1000 °C at a heating rate of 5 °C / min for secondary calcination after natural cooling. After being maintained for 2 h, it is naturally cooled to room temperature, and finally a bifunctional FeNi single atom catalyst based on carbon fiber is obtained. The actual catalyst is shown in the figure. Figure 1 shown.

[0023] Embodiment 2: This embodiment provides a Fe single atom catalyst obtained by parallel spinning technology, and the preparation method is as follows: (1) Add 3.94 g of dimethylimidazole, 3.36 g of zinc nitrate hexahydrate, and 120 mg of ferric nitrate nonahydrate into 600 mL of methanol. Stir for 12 h, wash with deionized water four times, and dry to obtain Fe-ZIF-8 seed crystals.

[0024] (2) Take 0.35 g Fe-ZIF-8 seed crystals, 0.07 g polyvinyl pyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N, N-dimethylformamide solvent to obtain spinning solution A; divide 5 mL of spinning solution A into two equal parts and place them in two spinning needle tubes respectively. Use two spinning needles arranged in parallel. The specifications of the two spinning needles are 0.62 mm inner diameter and 0.9 mm outer diameter. Electrospinning is carried out under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller is 12 cm. The spinning rate is 1 mL / L. At room temperature, Fe-containing nanofibers with a thickness of about 5 µm are obtained. Subsequently, it was placed in an air atmosphere and heated to 280 °C at a heating rate of 1 °C / min for pre-oxidation, maintained for 2 h, cooled naturally and then heated to 1000 °C at a heating rate of 5 °C / min for secondary calcination. After maintaining for 2 h, it was naturally cooled to room temperature to finally obtain a Fe single atom catalyst based on carbon fiber.

[0025] Embodiment 3: This embodiment provides a Ni single atom catalyst obtained by parallel spinning technology, and the preparation method is as follows: (1) Add 10.59 g of dimethylimidazole, 2.37 g of zinc nitrate hexahydrate, and 2.34 g of nickel nitrate hexahydrate into 600 mL of methanol. Stir for 12 h, wash with deionized water four times, and dry to obtain Ni-ZIF-8 seed crystals.

[0026] (2) Take 0.35 g Ni-ZIF-8 seed crystals, 0.07 g polyvinyl pyrrolidone and 0.14 g polyacrylonitrile and dissolve them in 2.45 g N, N-dimethylformamide solvent to obtain spinning solution B. Divide 5 mL spinning solution B into two equal parts and place them in two spinning needle tubes respectively. Use two spinning needles arranged in parallel. The specifications of the two spinning needles are 0.62 mm inner diameter and 0.9 mm outer diameter. Electrospinning is carried out under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller is 12 cm. The spinning rate is 1 mL / L. At room temperature, Ni-containing nanofibers with a thickness of about 5 µm are obtained. Subsequently, it was placed in an air atmosphere and heated to 280 °C at a heating rate of 1 °C / min for pre-oxidation, maintained for 2 h, cooled naturally and then heated to 1000 °C at a heating rate of 5 °C / min for secondary calcination. After maintaining for 2 h, it naturally cooled to room temperature to finally obtain a Ni single atom catalyst based on carbon fiber.

[0027] Embodiment 4: This embodiment provides a FeNi single-atom catalyst obtained by classical electrospinning technology, and the preparation method is as follows: (1) Add 3.94 g of dimethylimidazole, 3.36 g of zinc nitrate hexahydrate and 120 mg of ferric nitrate nonahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water and dry to obtain Fe-ZIF-8 seed crystals; add 10.59 g of dimethylimidazole, 2.37 g of zinc nitrate hexahydrate and 2.34 g of nickel nitrate hexahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water and dry to obtain Ni-ZIF-8 seed crystals.

[0028] (2) 0.35 g Fe-ZIF-8 seed crystals, 0.07 g polyvinyl pyrrolidone and 0.14 g polyacrylonitrile were dissolved in 2.45 g N, N-dimethylformamide solvent to obtain spinning solution A; 0.35 g Ni-ZIF-8 seed crystals, 0.07 g polyvinyl pyrrolidone and 0.14 g polyacrylonitrile were dissolved in 2.45 g N, N-dimethylformamide solvent to obtain spinning solution B. 2.5 mL spinning solution A and 2.5 mL spinning solution B were mixed and placed in a spinning needle tube with a spinning needle of inner diameter of 0.62 mm and outer diameter of 0.9 mm. Electrospinning was performed under a high voltage electric field of 18 kV. The distance between the spinning needle and the receiving roller was 12 cm. The spinning rate was 1 mL / L. At room temperature, FeNi bimetallic nanofibers with a thickness of about 5 µm were obtained. Subsequently, it was placed in an air atmosphere and heated to 280 °C at a heating rate of 1 °C / min for pre-oxidation, maintained for 2 h, cooled naturally and then heated to 1000 °C at a heating rate of 5 °C / min for secondary calcination. After maintaining for 2 h, it naturally cooled to room temperature to finally obtain a FeNi single-atom catalyst based on carbon fiber.

[0029] Embodiment 5: This embodiment provides a bifunctional FeNi single atom catalyst obtained by parallel spinning technology, and the preparation method is as follows: (1) Add 4.8 g of dimethylimidazole, 4.2 g of zinc nitrate hexahydrate and 120 mg of ferric nitrate nonahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water, and dry to obtain Fe-ZIF-8 seed crystals; add 12.87 g of dimethylimidazole, 3.5 g of zinc nitrate hexahydrate and 2.34 g of nickel nitrate hexahydrate to 600 mL of methanol, stir for 12 h, wash four times with deionized water, and dry to obtain Ni-ZIF-8 seed crystals.

[0030] (2) Take 0.49 g of Fe-ZIF-8 seed crystals, 0.07 g of polyvinyl pyrrolidone (Aladdin, P110607) and 0.14 g of polyacrylonitrile (Aladdin, P303197) and dissolve them in 2.8 g of N, N-dimethylformamide solvent to obtain spinning solution A; take 0.49 g of Ni-ZIF-8 seed crystals, 0.07 g of polyvinyl pyrrolidone and 0.14 g of polyacrylonitrile and dissolve them in 2.8 g of N, N-dimethylformamide solvent to obtain spinning solution B. The spinning solution A and the spinning solution B were placed in two spinning needle tubes respectively, and two spinning needles arranged in parallel and close to each other were used. The specifications of the two parallel spinning needles were 0.62 mm in inner diameter and 0.9 mm in outer diameter. Electrospinning was performed under a high voltage electric field of 22 kV, wherein the spinning solution A and the spinning solution B were both 2.5 mL, the distance between the spinning needle and the receiving roller was 15 cm, the spinning rate was 1.2 mL / L, and the nanofiber containing FeNi bimetallic was obtained at room temperature, with a thickness of about 5 µm. Subsequently, it was placed in an air atmosphere and heated to 280 °C at a heating rate of 2 °C / min for pre-oxidation, maintained for 3 h, and then heated to 950 °C at a heating rate of 6 °C / min for secondary calcination after natural cooling, and then naturally cooled to room temperature after 3 h, and finally a bifunctional FeNi single atom catalyst based on carbon fiber was obtained.

[0031] Characterization Example 1: The bifunctional FeNi single-atom catalyst obtained in Example 1 was observed under a scanning electron microscope. The morphology and structure are as follows: Figure 2 shown.

[0032] from Figure 2 It can be seen that Example 1 successfully synthesized a catalyst having a continuously distributed nanofiber structure.

[0033] Characterization Example 2: The bifunctional FeNi single-atom catalyst obtained in Example 1 was subjected to X-ray diffraction analysis. Figure 3 shown.

[0034] Figure 3 Only two broad diffraction peaks were observed, confirming that the metal in the catalyst existed in single-atom form.

[0035] Test Example 1: The electrochemical performance of the catalysts of Examples 1 to 3 was tested. The scan rate of the LSV test was 5 mV / s, and the rotation speed of the rotating disk electrode was 1600 rpm.

[0036] The specific process is as follows: Preparation of catalyst slurry: 2 mg of catalyst was placed in a centrifuge tube, 800 μL of ethanol and 5 μL of Nafion solution (perfluorosulfonic acid, Aladdin, N169478) were added, and ultrasonication was performed to form a uniformly dispersed slurry.

[0037] When performing ORR and OER tests, 5 μL of catalyst slurry was dripped onto the rotating disk electrode for 6 times. The catalyst loading was 0.3 mg / cm 2 The reference electrode was a calomel electrode, the counter electrode was a platinum wire electrode, and the electrolyte was a 1M potassium hydroxide solution. O2 was introduced into the electrolyte before the test for 1 h to achieve O2 saturation. The ORR and OER performance of the catalyst was tested using a CHI660E electrochemical workstation.

[0038] The data obtained is as follows Figure 4 As shown, the catalyst of Example 1 exhibits the best ΔE of 0.66 V, showing excellent bifunctional characteristics.

[0039] Embodiment 6: This embodiment provides a zinc-air battery, and the preparation method is as follows: Assemble a rechargeable zinc-air battery: the anode is a polished zinc sheet. According to the slurry preparation method described in Test Example 1, 400 μL of the catalyst slurry obtained in Example 1, Example 4 and Example 5 are respectively dripped onto a carbon cloth (Shengernuo Energy Mall, HCP330N, thickness 0.33 mm) as a cathode, and the electrolyte is composed of 6 M potassium hydroxide and 0.2 M zinc acetate.

[0040] The battery performance test was carried out using a CHI 1140E electrochemical workstation with a test scan rate of 5 mV / s.

[0041] The open circuit voltage and power density of the assembled rechargeable zinc-air battery are shown in Figure 5 and Figure 6 As shown in Figure 1, the open circuit voltage of the rechargeable zinc-air battery assembled with the catalyst of Example 1 as the air cathode reached 1.53 V, and the peak power density reached 252 mW / cm 2 , which is comparable to the performance of the zinc-air battery assembled by Example 5, but significantly better than the zinc-air battery assembled by the mixed catalyst prepared by Example 4. It is speculated that this result is due to the direct mixing of spinning solutions A and B in Example 4, which causes mutual concealment between the active ingredients, while the preparation methods of Examples 1 and 5 achieve full exposure of the bifunctional active sites, and the carbon nanofibers ensure the uniform distribution of the active sites and the excellent conductivity promotes the transfer of electrons. Figure 7As shown in Figure 2, the rechargeable zinc-air battery assembled with the catalyst of Example 1 as the air cathode exhibits excellent stability at different current densities. In addition, the battery has a long lifespan. -2 The constant current charge and discharge test was carried out at a current density of 1400 hours. Figure 8 ).

[0042] In summary, the present invention avoids the problem of covering between active components caused by the traditional physical mixing method for preparing bifunctional catalysts. In addition, the present invention realizes the interaction between the dual catalytic active sites, ensures the full exposure of the bifunctional active sites, and the carbon nanofibers ensure the uniform distribution of the active sites and the excellent conductivity promotes the transfer of electrons. A new method is provided for the cathode material for rechargeable zinc-air batteries.

[0043] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a battery cathode material, characterized in that: Fe-ZIF-8 seed crystals and Ni-ZIF-8 seed crystals are first prepared into spinning solutions and then placed in two spinning needle tubes arranged in parallel for electrospinning. They are then calcined at 950-1000°C to obtain catalysts. Catalyst slurry is made from the catalyst and dripped onto carbon cloth to obtain battery cathode materials.

2. The preparation method according to claim 1, characterized in that: The preparation method of the catalyst slurry comprises: mixing a catalyst, ethanol and a Nafion solution to obtain the catalyst slurry.

3. The preparation method according to claim 1 or 2, characterized in that: The electrospinning parameters are as follows: applied voltage is 18-22 kV, spinning rate is 1-1.2 mL / h, and receiving distance is 12-15 cm.

4. The preparation method according to claim 1 or 2, characterized in that: The preparation method of the catalyst consists of the following steps: Step 1: Mix zinc salt, iron salt and organic ligand and add them to a solvent to prepare Fe-ZIF-8 seed crystals; Mix zinc salt, nickel salt and organic ligand and add them to a solvent to prepare Ni-ZIF-8 seed crystals; Step 2: mixing the Fe-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution A; mixing the Ni-ZIF-8 seed crystals, polymer, and spinning solvent to obtain spinning solution B; Step 3: Spinning solution A and spinning solution B are placed in two spinning needle tubes respectively, and electrospinning is performed using spinning needles arranged in parallel to obtain nanofibers containing FeNi bimetallic; Step 4: pre-oxidize the FeNi bimetallic nanofibers prepared in step 3, then calcine at 950-1000° C., and obtain the catalyst after natural cooling.

5. The preparation method according to claim 4, characterized in that: In step 1, the zinc salt is zinc nitrate hexahydrate; the iron salt is iron nitrate nonahydrate; and the nickel salt is nickel nitrate hexahydrate.

6. The preparation method according to claim 4, characterized in that: In step 2, the polymers are polyacrylonitrile and polyvinyl pyrrolidone, and the spinning solvent is N, N-dimethylformamide; The mass ratio of the Fe-ZIF-8 seed crystal, the polymer, and the spinning solvent is 5-7:3:35-40; the mass ratio of the Ni-ZIF-8 seed crystal, the polymer, and the spinning solvent is 5-7:3:35-40.

7. The preparation method according to claim 4, characterized in that: In step 1, the mass ratio of zinc salt, iron salt and organic ligand is 28-35:1:33-40; the mass ratio of zinc salt, nickel salt and organic ligand is 2-3:2:9-11; the organic ligand includes dimethylimidazole; and the solvent includes methanol.

8. The preparation method according to claim 4, characterized in that: In step 4, the pre-oxidation heating rate is 1~2 ℃ / min, air atmosphere, and the pre-oxidation time is 2~3 h; the high-temperature calcination heating rate is 5~6 ℃ / min, nitrogen atmosphere, and the calcination time is 2~3 h.

9. The battery cathode material prepared by the method for preparing a battery cathode material according to claim 1.

10. Use of the battery cathode material prepared by the method for preparing the battery cathode material according to claim 1 in a rechargeable zinc-air battery.

Citation Information

Patent Citations

  • Method for preparing magneto-optical difunctional two parallel strand composite nanofiber bundle

    CN102433610A

  • Method for constructing photoelectricity double function two-stranded parallel nanometer fiber bundle

    CN102943317A

  • Preparation method of cobalt and nitrogen co-doped carbon nanofiber catalyst and application of cobalt and nitrogen co-doped carbon nanofiber catalyst

    CN110010909A

  • High-elastic moisture-absorbing antistatic PTT / PET composite fiber and preparation method thereof

    CN112538662A

  • Preparation method of metal organic framework / nanofiber with bead-like structure

    CN112981960A